Cardiorespiratory fitness levels and body mass index of pre-adolescent children and older adults during the COVID-19 pandemic - Raine, Lauren B.; Erickson, Kirk I.; Grove, George; Watrous, Jennifer N. H.; McDonald, Katherine; Kang, Chaeryon; Jakicic, John M.; Forman, Daniel E.; Kramer, Arthur F.; Burns, Jeffrey M.; Vidoni, Eric D.; McAuley, Edward; et al. (Frontiers in Public Health, 2023)
Introduction The social and behavioral effects of the COVID-19 pandemic have impacted the health and physiology of most people, including those never diagnosed with COVID-19. While the impact of the pandemic has been felt across the lifespan, its effects on cardiorespiratory fitness (commonly considered a reflection of total body health) of older adults and children may be particularly profound due to social distancing and stay-at-home advisories, as well as the closure of sport facilities and non-essential businesses. The objective of this investigation was to leverage baseline data from two ongoing clinical trials to determine if cardiorespiratory fitness and body mass index were different during COVID-19 relative to before COVID-19 in older adults and children. Methods Healthy older individuals (N = 593; 65–80 years) and 200 typically developing children (8–10 years) completed a graded maximal exercise test and had their height and weight measured. Results Results revealed that older adults and children tested during COVID-19 had significantly lower cardiorespiratory fitness levels than those tested before COVID-19 shutdowns (older adults: 30% lower; children: 53% lower; p's ≤ 0.001). In addition, older adults and children tested during COVID-19 had significantly higher BMI (older adults: 31.34 ± 0.57 kg/m2, p = 0.004; children: 19.27 ± 0.44 kg/m2, p = 0.05) than those tested before COVID-19 shutdowns (older adults: 29.51 ± 0.26 kg/m2, children: 18.13 ± 0.35 kg/m2). However, these differences in BMI did not remain significant when controlling for cardiorespiratory fitness. Discussion Results from this investigation indicate that the COVID-19 pandemic, and behavior changes taken to reduce potential exposure, may have led to lower cardiorespiratory fitness levels in older adults and children, as well as higher body mass index. These findings provide relevant public health information as lower cardiorespiratory fitness levels and higher body mass indexes recorded during the pandemic could have far-reaching and protracted health consequences. Public health guidance is needed to encourage physical activity to maintain cardiorespiratory fitness and healthy body composition. Clinical trial registration Older adults: https://clinicaltrials.gov/ct2/show/NCT02875301, identifier: NCT02875301; Children: https://clinicaltrials.gov/ct2/show/NCT03592238, identifier: NCT03592238.